Socio Economic Characteristics of Women Beedi Workers in Murshidabad District of West Bengal, India - Imran Sk; Md. Hasrat Ali (Archives of Current Research International, 2025)
This study investigates the socio-economic status of beedi workers in the Suti-II Block of Murshidabad District, West Bengal. A traditional agro-forest-based and unorganized industry in India is the beedi industry, where predominantly women laborers are engaged in beedi rolling. A sample of 100 respondents was selected through the Simple Random Sampling Without Replacement Method (SRSWOR). Data were collected using a pretested schedule. The results indicate that 56 per cent of respondents are aged between 30 -40 years, 50 per cent are illiterate, and 60 per cent earn between ₹3001 - ₹4000 per month. Approximately 64 per cent live in pucca houses, 56 per cent have 9 to 12 years of work experience and 86 per cent consider beedi rolling as their secondary occupation. The study highlights the challenging conditions faced by beedi workers, including low wages, limited educational opportunities, and arduous working conditions. The study suggests improved health education, minimum wages, enhanced legal protections, and increased awareness regarding the rights and welfare of beedi workers to better their socio-economic status.